Studi persepsi visual perempuan pengendara terhadap desain sepeda motor skuter matik di Indonesia - Linda Lukita; Achmad Syarief; Slamet Riyadi; Andar Bagus Sriwarno (Institut Seni Indonesia Yogyakarta, 2021)
This study is an evaluation of perception and identification of attractive scooter design by female motorcycle riders. Survey with questionaire using Likert scale was conducted on 150 female scooter riders who provided assesment of six scooter design representing design of scooter in Indonesia. Descriptive analysis results show that scooter designs in Indonesia have perception: quality, comfortable to use, can be used by all family members, fun to use, relax and easy, and give confidence, which included in physio, socio, and psycho-pleasure also only reached the visceral and behavioral stage.Female riders’ perception is inline with the female gender characteristics, communal and have high empathy or emotional skill. Attractive scooter design for female riders has ideo-pleasure related perception and is determined from the details of the product design. From the factor analysis, it is described the pleasurability factors has different perception for each design. Conclusion of this study is beside size, type, and design characters, total shape as well as the details of the shape from the scooter design are the things that will affect the perception of the female rider and may provide a different perception of pleasurability evaluation from the female riders.